Integrasi Nilai-Nilai Pancasila dalam Pembelajaran PKn untuk Membangun Karakter Cinta Tanah Air Siswa Sekolah Dasar - Bherrio Dwi Saputra (Mathematics Education Study Program, 2025)
This study aims to analyze how the integration of Pancasila values in Citizenship Education (PKn) can build the character of love for the homeland in elementary school students. Based on the results of observations, interviews, and documentation conducted, it was found that most teachers have made efforts to integrate Pancasila values into the learning activities. The values of love for the homeland and mutual cooperation became the main focus in the learning process, with teachers using various methods such as group discussions, simulations, and educational games. The application of Pancasila values is more focused on introducing theory rather than on practices that are relevant to the students' real-life experiences. The findings show that although teachers recognize the importance of experience-based learning, time and resource constraints remain the main challenges in implementation. Documentation indicates that the instructional modules developed include goals to build the character of love for the homeland, but their implementation has not sufficiently linked Pancasila values to the daily lives of students. This study recommends the development of more contextual and experience-based learning methods to strengthen the positive impact in building the character of love for the homeland.